Strategi Keberlanjutan Usaha Tahu dan Tempe di Kampung Tematik Tahu Tempe Gumregah Kota Semarang - Agung Maulana, Otniel Linuwih; wijaya, Atika (Journal of Education on Social Science (JESS), 2025)
The end of the thematic village program requires tofu and tempeh artisans to be independent in running their businesses. The numerous thematic villages that have experienced failure and have not continued to develop their potential are a result of the end of the thematic village program. One of the thematic villages that continues to develop its potential is the Tahu Tempe Gumregah Thematic Village. This research aims to gather information regarding the strategies and solutions of tofu and tempeh artisans in overcoming various problems to sustain their economy. This research is reviewed using the concept of community empowerment, which emphasizes the strategies employed by tofu and tempeh artisans in continuing their business. The method used in this research is qualitative, with data collection through observation, interviews, and literature study. The subjects of this research are tofu and tempeh artisans, who are the main informants, and the local government, who are supporting informants. Tofu and tempeh artisans emphasize independence in addressing the problems that arise. This can be seen from the research findings that the sustainability of tofu and tempeh businesses cannot be separated from the strategies and solutions implemented to address all issues. In running their business, tofu and tempeh artisans always pay attention to product quality, weather, effective marketing processes, and detailed financial management. Strategy is the key to the sustainability of the tofu and tempeh business.